WORKSHOP INTERAKTIF TERKAIT PENYAKIT COVID-19 DAN VARIANNYA BAGI PARA SISWA SEKOLAH MENENGAH ATAS [INTERACTIVE WORKSHOP RELATED TO COVID-19 AND ITS VARIANTS FOR HIGH SCHOOL STUDENTS] - Sugata, Marcelia; Jo, Juandy; Soewono, Effendi; Pinontoan, Reinhard; Litanto, Vivian; Victor, Hans; Abigail Christy, Suawa Natania; Vidian, Valerie; Sophiano, Theophilus; Febriani, Enjelia; Jan, Tan Tjie (Jurnal Sinergitas PKM & CSR, 2022)
An interactive workshop related to COVID-19 and its variants was held during the introduction of Biology Study Program, Pelita Harapan University to high school students. This activity was carried out online and was divided into two sessions. The first session was socialization about COVID-19 and its variants, while the second session was the time to play an online game called ATtack Covid Variant (ATCV). The success of this activity was measured based on the surveys given before and after the activity. The survey results showed that socialization and online game ATCV have succeeded in increasing students' knowledge and understanding of COVID-19 and its variants. In addition, the students were satisfied with the ATCV game because of the benefits obtained from this game, the rules are easy to understand, and the visuals of the game are attractive.Bahasa Abstract:Workshop interaktif terkait COVID-19 dan variannya dilaksanakan saat kegiatan perkenalan Program Studi Biologi, Universitas Pelita Harapan kepada siswa/i sekolah menengah. Dalam pelaksanaannya, kegiatan ini dilakukan secara daring dan dibagi menjadi dua sesi. Sesi pertama adalah sosialisasi tentang COVID-19 dan variannya, sedangkan sesi kedua merupakan waktu untuk melakukan permainan daring yang bernama ATtack Covid Variant (ATCV). Keberhasilan kegiatan ini diukur berdasarkan survei yang diberikan sebelum dan setelah kegiatan. Hasil survei menunjukkan bahwa kegiatan sosialisasi dan permainan daring ATCV berhasil meningkatkan pengetahuan dan pemahaman para siswa mengenai COVID-19 dan variannya. Selain itu, para siswa merasa puas dengan permainan ATCV karena manfaat yang diperoleh dari permainan ini, peraturan yang mudah dipahami, serta visual permainan yang menarik.